The roles of Islamic work ethics on knowledge sharing practices in a financial institution: a case study in Malaysia - Haza, Irwan; Abdul Hamid, Zabeda; Omar, Azura (2015)
Knowledge Sharing (KS) has been posited by many researchers to play an important role in organisation life cycles. Hence, the researcher is interested to discover what might be the mediating factors that would lead to KS practices within organisations. However, the existing literature focus on materialism and secularism on the KS notion and have not touched much on the religiosity concept as a possible mediating factor. In this paper, the researcher investigates the roles of Islamic Work Ethic (IWE) as a mediator which promotes KS intention among the employees of a financial institution in Malaysia, anonymously named Bank Co. The reason for choosing IWE to represent the work ethic to be studied is because Islam is the official religion of Malaysia and the majority of the staff of Bank Co are Malay Muslims. The researcher would like to determine whether IWE would leave to individual's intention to share knowledge within the organisation. The paper is a work in progress and will involve respondents from the organisation's branches in Peninsular and East Malaysia. The collected data will be analysed using Structural Equation Modelling (S.E.M.).